Pemetaan Standar Kompetensi Dan Kompetensi Dasar Mata Pelajaran Bahasa Inggris Siswa Di Kabupaten Bengkalis Dan Kepulauan Meranti Provinsi Riau - Hadriana ' (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
The purpose of this research are: (1) to get clear description of students’ success inachieving basic competence on National Final Examination; (2) identify factors that caused unabilityof the students to acquire basic standard competence stated by the government; and (3) formulatealternative solution to increase the students’ standard competence at Bengkalis and Kepulauan MerantiRegency. The sample of this research were choosen based on the area of the school, SMAN IBengkalis, SMAN I Tebing Tinggi and SMAN Rangsang. The object of the research is English. Therewere two kinds of data needed in this research. Primary data gained from indepth interview,observation and questionaire, while secondary data obtained from documentation study. The result ofthe research indicated that some of the eight aspects stated by National Standard of Education were notapplied well, so it needs improvement.